(3GdGZfjI GdTYHjI ddGWaGd aj efWbI HfJ LHjds - (3HRj, RjfHs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2001)
(3JSYi GdOQGSI Edi QDjI EMOi CSS Jchjf GdTNUjI dCHfGA efWbI HfJ LHjd HcGed ehQhKGJgG GdCNdGbjI, GdKbGajI, hGdGLJeGYjI, ceG JSYi ddYKhQYdi GdechfGJ GdJQHhjI ddCZfjI GdTYHjI hOhQgG GdJYdjej aj Jchjf TNUjI GdWad, hJMOjO GdYfGUQ GdSdHjI hGdEjLGHjI GdJj JfJL YfgG(B. (3HGdEVGaI Edi GdOhQ GdJQHhj JSYi GdOQGSI Edi JMOjO GdOhQ GdfaSj, hGdOdGdGJ GdOjfjI, GdCSQjI, GdGbJUGOjI, GdGLJeGYjI, hGdJQHhjI, dgPg GdCZfjI(B. (3EYoJeO GdefgL GdJGQjNj hJbfjI JMdjd GdeVehf, EfWdGbkG ef JLejY CZGfj GdCWaGd hJhKjbgG, hef Ke ELQGA GdebGHdGJ eY GdCegGJ, aj efWbI HfJ LHjd LfhH dHfGf(B. (3HjfJ GdfJGFL Cf GdCZGfj GdTYHjI heG JMhjg ef eYGf hCgOGa JdYH OhQkG aj JfTFI GdWad, agj oJSJNOe dCgOGa JQHhjI hRQY bje GLJeGYjI SGFOI, MjK Jbhe HOhQ GdehLg dYbd GdWad, hJYJHQ GdghjI HMO PGJgG ef NdGd JeKjdgG dfXGe bje eJcGed , JYHjQkG UGObkG Yf PGJ GdWad hGdCgd ef NdGd eG JMedg ef OdGdGJ OjfjI, ELJeGYjI, hJQHhjI(B. (3aVdkG Yf CfgG Cge YGed dfbd GdJQGK GdTYHj ddWad, hJJahb Ydi cGaI hSGFd heDSSGJ GdJfTFI GdGLJeGYjI GdCNQi NGUI aj GdeLJeYGJ GdJbdjOjI(B. (3HGdEVGaI Edi GdOhQ GdEjLGHj GdPj JdYHg GdCZfjI GdTYHjI HEjUGdgG GdeaGgje hGdbje, HQR dOjgG LGfH SdHj HJQcjR eaGgje GdYOGhGJ GdGLJeGYjI hGdYUHjI, RQY GdNha ef GdCNQ, EXgGQ GdJaGhJ Hjf GdPchQ hGdEfGK hJMOjO GdOhQ GdhXjaj dgeG OGNd GdeLJeY(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3HfJ LHjds; Bint Jbeil; Bint Jbeil; Children; Enfants; L$1 (Benseignement de La Musique, des chansons et la dances; Teaching Music & Songs &Dance; (3GdCWaGds; (3JYdje GdehSjbi hGdCZGfj hGdQbUs